Women participating in sport: tensions rising from negotiations of aging, gender norms, and personal responsibility for health in later life - van Wyk, Paula M.; Seguin, Hannah; Dionigi, Rylee A.; Weir, Patti L.; Horton, Sean (Frontiers in Sports and Active Living, 2025)
IntroductionOlder women have typically faced systemic exclusion from sport, often a result of intersecting age- and gender-based norms and/or constraints. This study investigated how 22 women (mean age 61 years) participating in recreational or competitive sport understood and experienced their participation in relation to societal expectations of aging, gender, and maintaining health and wellbeing.MethodsThe women, aged 52–77 years, each participated in a semi-structured interview to explore their perspectives on aging, disability, societal perceptions, and sport engagement. Interviews were audio-recorded, transcribed, anonymized, and analyzed using reflexive thematic analysis, emphasizing researcher subjectivity and iterative theme development.ResultsThe women framed their sport involvement as a moral and disciplined practice, aligning with neoliberal ideals of personal responsibility and self-management for health in later life. However, their narratives also highlighted systemic barriers, such as professional demands, caregiving responsibilities, and gendered norms, that constrained their participation. This “double barrier” of age and gender norms produced a tension between perceived agency and structural exclusion.DiscussionWhile older women actively asserted responsibility for their health and engagement, their experiences revealed that structural inequities related to age and gender expectations, not personal failings, often limited participation.ConclusionThese findings challenge responsibility-centred narratives and call for inclusive sport policies that account for the socio-cultural and institutional barriers shaping older women's experiences in sport and exercise contexts.